A redescription of Polystoma africanum Szidat, 1932 (Monogenea: Polystomatidae) - Aisien, Martins S. O.; Preez, Louis H. Du (Zootaxa, 2009)
Polystoma africanum was originally described from a single specimen recovered from the common African toad, Amietophrynus regularis. The parasite has also been reported from the Angola river frog, Amietia angolensis, in Ethiopia; the Mascarene ridged frog, Ptychadena mascareniensis, in Uganda; and Ptychadena sp. in Zaire. One of the characters ascribed to this species was the lack of caecal anastomoses. Based on this and other characteristics, other polystomes from frog species like Pty. mascareniensis have been identified as P. africanum. A large collection of parasite specimens retrieved from A. regularis collected in Nigeria allowed a thorough re-examination of the species. A good proportion of the specimens (37%) correspond closely with the type in lacking intercaecal anastomoses. Other specimens showed considerable variation in this regard by possessing one to four intercaecal anastomoses. An unusual feature observed in several specimens is where two adjacent medial diverticula on one side join to form a loop. The type specimen also has a loop. The handle and guard of the hamuli are well separated, as in the type specimen from Liberia, and in other specimens from A. regularis (syn. Bufo regularis) in Uganda. The mean hamuli length of 388μm is close to the 370μm recorded for the type species, but this value is considerably smaller than the 459μm recorded for the specimens from Pty. mascareniensis in Uganda. On the basis of the aforementioned and invoking strict host specificity, we conclude that P. africanum is exclusively parasitic in A. regularis, and that the polystomes retrieved from Pty. mascareniensis from Uganda and a Ptychadena sp. from Zaire are most likely Polystoma pricei. The materials from A. angolensis most likely represent another species.